(X-4)10=7x+11

Simple and best practice solution for (X-4)10=7x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-4)10=7x+11 equation:


Simplifying
(X + -4) * 10 = 7x + 11

Reorder the terms:
(-4 + X) * 10 = 7x + 11

Reorder the terms for easier multiplication:
10(-4 + X) = 7x + 11
(-4 * 10 + X * 10) = 7x + 11
(-40 + 10X) = 7x + 11

Reorder the terms:
-40 + 10X = 11 + 7x

Solving
-40 + 10X = 11 + 7x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '40' to each side of the equation.
-40 + 40 + 10X = 11 + 40 + 7x

Combine like terms: -40 + 40 = 0
0 + 10X = 11 + 40 + 7x
10X = 11 + 40 + 7x

Combine like terms: 11 + 40 = 51
10X = 51 + 7x

Divide each side by '10'.
X = 5.1 + 0.7x

Simplifying
X = 5.1 + 0.7x

See similar equations:

| n^2+18n+96=0 | | n^2+18+96=0 | | 8-M=3M+16 | | 3x+51/4=3 | | 3xy+4xy+5x(5x)y+6xy(2)= | | 4(x-2)=8x-(8+4x) | | Y=20x+100 | | 6x/9=18 | | 4x^2+15x-10=0 | | 4a+4=a | | 3x+48/8=3 | | 7=w+3 | | -4v-10=-v+2 | | .15x^2-3x+30=0 | | -15y+-10y= | | (x(a-1)+a)(x(b-1)+b)=-2x+bx+ax+a+b | | 10-(2x+4)=7-3x | | -12u-18=-12u-18 | | 1-4x^2=-8 | | x^3abc-x^3ab+3x^2abc-x^3ac+x^3a-2x^2ac-2x^2ab+3xabc-x^3bc+x^3b-2x^2bc+x^3c-x^3+x^2c+x^2b-xbc+ax^2-axc-abx+abc-xa+3x-xb-xc-a-b-c=0 | | 4.62(2.64x+8.25)=0 | | 8x+9y=48 | | 2(n+1)+1=(2n-5)+(n-2) | | 7y-13-8=5y+9-9y | | 9(z+1)-2(z-3)=3(z-4)+3(z-2) | | 10t-22=10t-15 | | 3x^2-90x+450=0 | | 8x^2+8x-9x-9=0 | | -4t-4=-7t-4 | | (d^2-d+5)-(-d^2+d+5)= | | 120=2a-(15-7a) | | 2w-10=2w+10 |

Equations solver categories